2000
DOI: 10.1128/iai.68.2.999-1003.2000
|View full text |Cite
|
Sign up to set email alerts
|

Role of Listeriolysin O in Cell-to-Cell Spread of Listeria monocytogenes

Abstract: Listeria monocytogenes is a facultative intracellular bacterial pathogen that escapes from a host vacuolar compartment and grows rapidly in the cytosol. Listeriolysin O (LLO) is a secreted pore-forming protein essential for the escape of L. monocytogenes from the vacuole formed upon initial internalization. However, its role in intracellular growth and cell-to-cell spread events has not been testable by a genetic approach. In this study, purified six-His-tagged LLO (HisLLO) was noncovalently coupled to the sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
163
0
6

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(175 citation statements)
references
References 15 publications
6
163
0
6
Order By: Relevance
“…Listeriolysin O (LLO) is the main bacterial determinant responsible for the escape of L. monocytogenes from primary and secondary vacuoles 113,114 and one of its major virulence factors. 115 The gene that encodes LLO (hly) was the first virulence gene identified in Listeria, and is part of a locus that contains the main virulence genes (prfA, plcA, hly, mpl, actA and plcB).…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
“…Listeriolysin O (LLO) is the main bacterial determinant responsible for the escape of L. monocytogenes from primary and secondary vacuoles 113,114 and one of its major virulence factors. 115 The gene that encodes LLO (hly) was the first virulence gene identified in Listeria, and is part of a locus that contains the main virulence genes (prfA, plcA, hly, mpl, actA and plcB).…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
“…6,80 As discussed earlier, LM enters the APC through phagocytosis, and escapes into the host cytosol by perforating the phagosomal membrane through the action of a cytolysin, listeriolysin O (LLO). 36,37 A sequence rich in proline, glutamic acid, serine and threonine (PEST) at the amino terminus of LLO is thought to control the production of LLO. 81 Others found that the γ-interferon-inducible lysosomal thiolreductase (GILT) is responsible for the activation of LLO in vivo.…”
Section: The Role Of Llo In the Battle Against Cancermentioning
confidence: 99%
“…36,37 Once in the cytosol, the endogenously produced TAA are processed, transported into the endoplasmic reticulum (ER) for loading onto major histocompatibility complex (MHC) class I molecules and presented as short peptides via the MHC class I pathway, resulting in the activation of CD8 T-cells. However, most LM are actually destroyed and processed in the phagolysosome.…”
mentioning
confidence: 99%
“…45 The protein was purified using Ni-NTA superflow (Qiagen, CA) on an FPLC system (Bio-Rad, Biologic HR Chromatography System) as previously described. 46 Typically, from a 1 l culture, B20 mg of purified LLO was obtained.…”
Section: Recombinant Llo Purificationmentioning
confidence: 99%